2021
DOI: 10.1016/j.antiviral.2021.105147
|View full text |Cite
|
Sign up to set email alerts
|

A tetrameric ACE2 protein broadly neutralizes SARS-CoV-2 spike variants of concern with elevated potency

Abstract: The SARS-CoV-2 receptor angiotensin converting enzyme 2 (ACE2) was previously engineered into a high affinity tetravalent format (ACE2-Fc-TD) that is a potential decoy protein in SARS-CoV-2 infection.We report that this protein shows greatly enhanced binding to SARS-CoV-2 spike proteins of the SARS-CoV-2 variants of concern B.1.1.7 (alpha variant, originally isolated in the United Kingdom) and B.1.351 (beta variant, originally isolated in South Africa) with picomolar compared with nanomolar Kd values. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Since the publication of our methodology for the fast prediction of Spike/ACE2 binding affinities, multiple publications have reported the dissociation constants of prolific variants of the SARS-CoV-2 Spike protein with ACE2. With these data in hand, our model can be updated to better predict the binding affinity of emerging variants of concern such as the Omicron variant . Briefly, for each variant, the SARS-CoV-2 Spike protein (consisting of the Spike RBD region binding with ACE2) crystal structure (PDB: 7KMB) was mutated using the PyMol mutagenesis tool, making sure to choose the lowest-energy rotamer of the mutated residue.…”
Section: Methodsmentioning
confidence: 99%
“…Since the publication of our methodology for the fast prediction of Spike/ACE2 binding affinities, multiple publications have reported the dissociation constants of prolific variants of the SARS-CoV-2 Spike protein with ACE2. With these data in hand, our model can be updated to better predict the binding affinity of emerging variants of concern such as the Omicron variant . Briefly, for each variant, the SARS-CoV-2 Spike protein (consisting of the Spike RBD region binding with ACE2) crystal structure (PDB: 7KMB) was mutated using the PyMol mutagenesis tool, making sure to choose the lowest-energy rotamer of the mutated residue.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a concern that VOCs and/or VOIs may reduce the efficacy of the anti-SARS-CoV-2 induced-antibodies or eventually evade them completely ( Leach et al, 2021 ; Salleh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study by the same group revealed that the tetrameric format greatly enhanced VOCs neutralization. [143] …”
Section: Promising Bionanotechnology Approaches To Achieve Improved T...mentioning
confidence: 99%